2019
DOI: 10.1002/acm2.12792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the IAEA‐TRS 483 protocol for the dosimetry of small fields (square and stereotactic cones) using multiple detectors

Abstract: The IAEA TRS 483 protocol1 for the dosimetry of small static fields in radiotherapy was used to calculate output factors for the Elekta Synergy linac at the Australian Radiation Protection and Nuclear Safety Agency (ARPANSA). Small field output factors for both square and circular fields were measured using nine different detectors. The “corrected” output factors (ratio of detector readings multiplied by the appropriate correction factor from the protocol) showed better consistency compared to the “uncorrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
5
7
1
Order By: Relevance
“…The application of TRS‐483 correction factors reduced the variation in measured output factors between the six individual detectors in this study, with the exceptions of the PTW 60016 diode for 6‐MV and 6‐FFF beams and the IBA PFD3G for 10‐MV and 10‐FFF beams. This agrees with the work of Smith et al 12 . who found that the PTW 60016 diode corrected output factors were lower than the average of other detectors for a 15 mm cone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The application of TRS‐483 correction factors reduced the variation in measured output factors between the six individual detectors in this study, with the exceptions of the PTW 60016 diode for 6‐MV and 6‐FFF beams and the IBA PFD3G for 10‐MV and 10‐FFF beams. This agrees with the work of Smith et al 12 . who found that the PTW 60016 diode corrected output factors were lower than the average of other detectors for a 15 mm cone.…”
Section: Discussionsupporting
confidence: 93%
“…The corrected output factors measured with the other five detectors agreed well. This follows the results of Smith et al., 12 who found that TRS‐483 correction factors reduced the variation in output factors for a variety of detectors. The application of TRS‐483 correction factors to small field measurements is a valid method to determine accurate output factors, however multiple detectors should be used to reduce the uncertainty of the results and limit the effect of variation amongst individual detectors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Besides the historical firm [28] it should be underlined that the number of vendors, such as [29][30][31] has increased in the past decade. The next important development is the growing diffusion of a commercial dosimeter, the PTW60019 microDiamond, which has become a reference dosimeter after many comparative studies with other types of dosimeters [32][33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that the StereoCalc is truly independent, a set of relative measurements including multiple depth dose curves and output factors (OFs) were obtained, following the new dosimetry formalism proposed by the International Atomic Energy Agency TRS‐483: dosimetry of small static fields used in external beam radiotherapy. 8 , 9 This is the first international code of practice dedicated to the dosimetry of small fields for specialized radiotherapy equipment able to produce small fields and for conventional LINACs with and without flattening filter for photon fields up to 10 MV.…”
Section: Introductionmentioning
confidence: 99%